Understanding the Role and Challenges of ELL Departments at Public Schools: An inquiry from pre-service teachers’ perspectives - Nilufer Guler; Jessica Christman; Jenna Larson; Ariane Smith (The Advocate, 2015)
Number of English Language Learners (ELLs) at U.S. public schools is increasing each year, and putting more and more mainstream teachers in need of teaching to this student group. ELLs are a vulnerable group with low academic success level and high drop-out rate. Preparing in-service and pre-service teachers to teach these students is crucial since ELLs need special accommodations and scaffolding to be more successful academically. In addition, research on mainstream teachers and ELL students have uncovered that mainstream teachers may have some wrong and unwelcoming perceptions of ELLs. This study investigates how taking a class on ELL education affects the pre-service teachers’ perceptions of this student group. In addition, this study reveals some of the most common challenges ELL teachers come across at public schools. The results uncovers that taking even only one class on ELL education changes pre-service teachers’ perceptions of ELLs positively. At the end of the paper, some pedagogical implications for preparing pre-service teachers to teach ELLs are given.